Triple Identity: Culturally Conditioned Misunderstanding; Multiculturalism; Territoriality - Aranibar-Ramos, Edgar Romario (2023)
In Peruvian territory there is a notion of the existence of different cultures, but not in its entirety. In this way, the search for knowledge is not limited to cultural patterns typical of the current regulations of a State or abstract theories. Thereby, the perspective is developed from three realities: urban, rural and uncontacted sectors; with the aim of deepening the need to consider multiculturalism as a starting point in intercultural crimes, for the sake of cultural heterogeneity and social realism. Thus, the normative application of a dominant sector on the interests of minorities -rural and uncontacted sector- presents conceptual and practical limitations in the Peruvian domestic reality. In this line, a holistic and coherent vision is proposed to practical assumptions from the hand of two sciences: anthropology and law; in order to emphasize the existence of a culturally independent society as an autonomous entity as result of customary law and learning, as a synonym of culture and necessity in the face of the existence of legal loopholes that intend to impose a restrictive model of rights, relegating respect for the right to dignity, principle of territoriality, autonomy, predictability and identity